The Power Rule of Exponents states that for any positive numbers a and b, and any positive integer n, (a^b)^n is equal to a^(b*n).
In this case, a is 7, b is 2, and n is 2. So, using the Power Rule of Exponents, we have:
(7^2)^2 = 7^(2*2)
= 7^4
Therefore, the exponent of (7^2)^2 in exponential simplest form, with the base remaining 7, is 4.
Using the Power Rule of Exponents, what is the exponent of (7^2)^2 in exponential simplest form if the base remains 7?(1 point)
27 answers
What is the exponent in an equivalent form of the expression (8^3)^3 ?(1 point)
Using the Power Rule of Exponents, we have:
(8^3)^3 = 8^(3*3)
= 8^9
Therefore, the exponent in an equivalent form of the expression (8^3)^3 is 9.
(8^3)^3 = 8^(3*3)
= 8^9
Therefore, the exponent in an equivalent form of the expression (8^3)^3 is 9.
Applying the Power Rule of Exponents, what is the exponent in an equivalent form of ((1/6)^3)^3 ? Answer with a whole number for the exponent where the base is 1/6 .(1 point)
Using the Power Rule of Exponents, we have:
((1/6)^3)^3 = (1/6)^(3*3)
= (1/6)^9
Therefore, the exponent in an equivalent form of ((1/6)^3)^3, with the base being 1/6, is 9.
((1/6)^3)^3 = (1/6)^(3*3)
= (1/6)^9
Therefore, the exponent in an equivalent form of ((1/6)^3)^3, with the base being 1/6, is 9.
Apply the Power Rule of Exponents to simplify (4^2)^2 as a whole number.(1 point)
Using the Power Rule of Exponents, we have:
(4^2)^2 = 4^(2*2)
= 4^4
Therefore, the simplified form of (4^2)^2 as a whole number is 4^4, which is equal to 256.
(4^2)^2 = 4^(2*2)
= 4^4
Therefore, the simplified form of (4^2)^2 as a whole number is 4^4, which is equal to 256.
Apply the Power Rule of Exponents to simplify (4^2)^3 as a whole number.(1 point)
Using the Power Rule of Exponents, we have:
(4^2)^3 = 4^(2*3)
= 4^6
Therefore, the simplified form of (4^2)^3 as a whole number is 4^6, which is equal to 4096.
(4^2)^3 = 4^(2*3)
= 4^6
Therefore, the simplified form of (4^2)^3 as a whole number is 4^6, which is equal to 4096.
Using the Power Rule of Exponents, what is an equivalent form of (2^8)^2 ?(1 point)
2(8 divisionsign 2)
2(8 - 2)
2(8 + 2)
2(8 x 2)
2(8 divisionsign 2)
2(8 - 2)
2(8 + 2)
2(8 x 2)
Using the Power Rule of Exponents, we have:
(2^8)^2 = 2^(8*2)
= 2^16
Therefore, an equivalent form of (2^8)^2 is 2^16.
(2^8)^2 = 2^(8*2)
= 2^16
Therefore, an equivalent form of (2^8)^2 is 2^16.
choose from here 2(8 divisionsign 2)
2(8 - 2)
2(8 + 2)
2(8 x 2)
2(8 - 2)
2(8 + 2)
2(8 x 2)
The equivalent form of (2^8)^2 is 2^(8 x 2).
Using the Power Rule of Exponents, what is an equivalent form of (6^6)^3 ? (1 point)
Using the Power Rule of Exponents, we have:
(6^6)^3 = 6^(6*3)
= 6^18
Therefore, an equivalent form of (6^6)^3 is 6^18.
(6^6)^3 = 6^(6*3)
= 6^18
Therefore, an equivalent form of (6^6)^3 is 6^18.
Using the Power Rule of Exponents, what is an equivalent form of ((1/2)^10)^2 ?(1 point) Responses
Using the Power Rule of Exponents, we have:
((1/2)^10)^2 = (1/2)^(10*2)
= (1/2)^20
Therefore, an equivalent form of ((1/2)^10)^2 is (1/2)^20.
((1/2)^10)^2 = (1/2)^(10*2)
= (1/2)^20
Therefore, an equivalent form of ((1/2)^10)^2 is (1/2)^20.
is (1/2)^20 equal to (1/2)^(10-2)?
No, (1/2)^20 is not equal to (1/2)^(10-2).
(1/2)^20 is equal to (1/2)*(1/2)*(1/2)*(1/2)*... (20 times)
(1/2)^(10-2) is equal to (1/2)^8, which means multiplying (1/2) by itself 8 times.
These two expressions are not equal.
(1/2)^20 is equal to (1/2)*(1/2)*(1/2)*(1/2)*... (20 times)
(1/2)^(10-2) is equal to (1/2)^8, which means multiplying (1/2) by itself 8 times.
These two expressions are not equal.
Apply the Power Rule of Exponents to form an equivalent expression of (2^6)^2 .(1 point)
Using the Power Rule of Exponents, we have:
(2^6)^2 = 2^(6*2)
= 2^12
Therefore, an equivalent expression of (2^6)^2 is 2^12.
(2^6)^2 = 2^(6*2)
= 2^12
Therefore, an equivalent expression of (2^6)^2 is 2^12.
What is the result of (2^3)^3 using the Power Rule of Exponents?
Using the Power Rule of Exponents, we have:
(2^3)^3 = 2^(3*3)
= 2^9
Therefore, the result of (2^3)^3 using the Power Rule of Exponents is 2^9.
(2^3)^3 = 2^(3*3)
= 2^9
Therefore, the result of (2^3)^3 using the Power Rule of Exponents is 2^9.
as a whole?
The result of (2^3)^3, as a whole number, using the Power Rule of Exponents is 512.
Oki tysm ill see you again some time bye!
You're welcome! I'm glad I could help. Remember, I'm here to assist you whenever you need. Goodbye and take care!